Design of Drug Recovery Scheme Based on Path Optimization. Issue 1 (June 2020) - Wang, Zhaojiu; Liu, Xiaohan; Wang, Sixian; Meng, Xiangyu; Liu, Chongshuang; Tang, Changyu
Abstract: Countries with the upsurge of garbage sorting, all over the Word attach importance to the recycling of expired medical products. The design of reverse logistics network of expired drugs has become a key problem in the field of pharmaceutical safety. Considering that expired drugs can not be recovered effectively, this paper studies the problem of drug recovery logistics by using TSP model and mileage saving model. It is beneficial to arouse the enthusiasm of enterprises and residents to participate in the recovery of expired drugs, thus reducing the production and manufacturing costs of pharmaceutical enterprises in China and reducing the pollution of waste drugs to the environment.